PENGARUH KOMUNIKASI INTERPERSONAL DALAM MENURUNKAN PROBLEM TEKANAN EMOSI BERBASIS GENDER - Hasanah, Hasyim (Sawwa: Jurnal Studi Gender, 2015)
This research seeks to investigate the contribution interpersonal communication to reduce emotion problem pressure college student in IAIN special programme. Five major dimension of interpersonal comÂmunication are openness, emphaty, supportiveness, positiveness and equality, were derived from a humanistic perception. Emotion problem pressure was defined in term pleasant and unpleasant emotion, besides from four conditional are stimulate, feelness, internal responshipness and behavior types. Sixty six subjects were involved in study, subject were devided into three programmes, 17 subject PKPA, 24 subject FUPK-TH and 25 subject FUPK-TP. To find the contribution between interpersonal communication and emotion problem pressure it used simple regression method, and different effect variables using t-test method. The result of this study shows that interpersonal communication has a real effect to reduce emotion problem pressure (Fh = 7,966 Ft = 6,302, p = 0,05; R2 = 0,910), the contribution variation of interpersonal communication is high (91,0%) and 0,9 explained by other variation models in independent variable. The contribution effect, male is higher than female (tm = 16,065 tf = 11,660). In conclusion, interpersonal communication has the contriÂbution effect to reduce emotion problem pressure of callege student in IAIN special programme.